Accounting for U.S. Real Exchange Rate Changes - Engel, Charles (Journal of Political Economy, 1999)
This study measures the proportion of U.S. real exchange rate movements that can be accounted for by movements in the relative prices of nontraded goods. The decomposition is done at all possible horizons that the data allow‐from one month up to 30 years. The accounting is performed with five different measures of non‐traded‐goods prices and real exchange rates, for exchange rates of the United States relative to a number of other high‐income countries in each case. The outcome is surprising: relative prices of movement of U.S. real exchange rate with Japan. The possibility of mismeasurement of traded‐goods prices is explored.